2020
DOI: 10.26623/jreb.v13i2.2690
|View full text |Cite
|
Sign up to set email alerts
|

Determinan Penyerapan Anggaran Dengan Komitmen Organisasi Sebagai Moderating Variable

Abstract: <p><em>This study aims to analyze the effect of budget planning, human resource competence and budget evaluation on budget absorption through organizational commitment as a moderating variable</em><em>.</em><em> The population in this study were 35 district / city offices of the Ministry of Religion in Central Java and 1 Regional Office of the Ministry of Religion, Central Java Province. The sample was 106 respondents. The respondents are financial management employees, name… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
1
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 7 publications
0
2
1
4
Order By: Relevance
“…The results of research by Koriatmaja et al, (2020), Putri et al, (2021), Lannai & Asbi (2020), Sari et al, (2019) and Oktaria et al, (2020) found that budget planning has a positive effect on budget absorption. In contrast to the research results of Sirin et al, (2020) which found that budget planning has a negative effect on budget absorption. Other results are also shown by research by Ardianne et al, (2020) and Salwah (2019) found that budget planning has no effect on budget absorption.…”
Section: Figure 1 Unnes 2017-2021 Budget Realizationcontrasting
confidence: 85%
See 1 more Smart Citation
“…The results of research by Koriatmaja et al, (2020), Putri et al, (2021), Lannai & Asbi (2020), Sari et al, (2019) and Oktaria et al, (2020) found that budget planning has a positive effect on budget absorption. In contrast to the research results of Sirin et al, (2020) which found that budget planning has a negative effect on budget absorption. Other results are also shown by research by Ardianne et al, (2020) and Salwah (2019) found that budget planning has no effect on budget absorption.…”
Section: Figure 1 Unnes 2017-2021 Budget Realizationcontrasting
confidence: 85%
“…Budget Planning is the initial process in the budget implementation period in government agencies. According to Sirin et al, (2020) budget planning is an important element in an organization. Budget planning describes the work plan to be implemented in the coming period.…”
Section: Budget Planningmentioning
confidence: 99%
“…Peraturan Pemerintah Nomor 45 Tahun 2013 tentang tata cara pelaksanaan anggaran pendapatan dan belanja negara diubah menjadi PP Nomor 50 Tahun 2018 tentang penggunaan APBN, untuk mendukung percepatan dan modernisasi anggaran secara lebih profesional, terbuka, efektif, efisien, dan bertanggung jawab dengan tetap memperhatikan prinsip pengelolaan keuangan negara yang baik. Pemahaman yang baik mengenai mekanisme Penyusunan Anggaran belanja Kementerian/Lembaga sangat penting untuk dipahami oleh berbagai pihak, utamanya dalam rangka pencapaian tujuan dan fungsi satuan kerja yang optimal (Kurnia Illahi & Saifulloh, 2021;Paputungan et al, 2017;Sirin et al, 2020;Wibawa & Wibowo, 2021).…”
Section: Pendahuluanunclassified
“…Penelitian ini didukung oleh (Astuti et al, 2018;Delia et al, 2021;Gagola et al, 2017;Paputungan et al, 2017;Priyantono et al, 2017;Suhipna & Winarti, 2013) yang menyatakan bahwa anggaran dapat terserap dengan efektif dan efisien jika ada keterlibatan para kuasa anggaran dan pengguna anggaran dalam proses perencanaan anggaran. Selain itu juga, penyerapan anggaran dapat efektif jika dalam proses pembuatan anggaran, dilakukan revisi guna mengoptimalkan anggaran menjadi terserap 100% pada akhir periode (Delia et al, 2021;Oktaliza et al, 2020;Ramdhani & Anisa, 2017;Sirin et al, 2020;Wiansyah & Mulyani, 2021) Berdasarkan uraian di atas dapat hipotesis penelitian adalah Pengaruh partisipasi penyusunan anggaran dan revisi anggaran terhadap efektivitas penyerapan anggaran di Balai Besar Konservasi Sumber Daya Alam Jawa Barat.…”
Section: Kajian Pustaka Dan Pegembangan Hipotesisunclassified
“…Manusia adalah unsur terpenting dalam keberhasilan suatu organisasi. Dikatakan oleh (Sirin et al, 2020) bahwa asset organisasi yang paling penting dan harus diperhatikan oleh manajemen adalah manusia (sumber daya manusia atau human resource).…”
Section: Sumber Daya Manusiaunclassified